Kontribusi dan Peran Ulama Mencegah Hadits Maudhu - Afrizal Nur (Lembaga penelitian dan Pengabdian kepada Masyrakat, 2013)
The spread of hadith maudhu ‘ is an issue that has recently occurred. False hadith is hadith which is made Suyuti up to Shaykh Nasir al-Din al - Bani, but the effort and attention should be continued for those who have the authority science by way of reviewing, writing, discussions, seminars about the existence of the hadiths maudhu ‘, so as to minimize the spread and practice of hadiths maudhu ‘ by society. In addition to the hadith as sources of law after the Qur’an, hadith is also a second source of interpretation bil ma’tsur, and in the hadith of the interpretation function is to explain global verses, verses that explain abstruse, paragraph absolute - verse, and others. So if the hadiths that are used for the hadith interprets maudhu ‘ then this will damage the interpretation.